The unity of linguistic meaning - Collins, John. (Oxford : Oxford University Press, 2011)
John Collins presents an analysis of the problem of the unity of the proposition - how propositions can be both single things and complexes at the same time. He surveys previous investigations of the problem and offers his own solution, which is defended from both philosophical and linguistic perspectives.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: English language -- Prepositions; English language -- Semantics